Evaluasi Kinerja IMAG pada Pembangkit Listrik Tenaga Mikrohidro Cokro Tulung Kabupaten Klaten - Mahalla; Suharyanto; M. Isnaeni B. S. (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
IMAG (Induction Motor as Asynchronous Generator) or induction motor that is used as an asynchronous generator having been widely used in micro-hydro Power Plant (MHP)usually in small capacity, i.e below 100 Kw. The reason for the widespread popularity of induction generator is owing to it’s capability to generate the power from variable speed as well as constant speed prime movers, low unit cost, reduced maintenance, rugged and brushless rotors, absence of a separate d.c. source for excitation, absence of moving contacts, inherent overload protection, improved performance due to low transient impedance, natural protection against short circuit, there are many on the market etc. Their main disadvantage is poor voltage and frequency regulation under varying load and speed. Imag performance evaluation needs to be analyzed including it is voltage stability analysis and frequency analysis in expenses. Based on the analysis of the system in general, efficiency is 47,38% total imag and positions the turbine room and Imag are still far from flood-free area, so a high fall (head) can be increased from 1 m up to 2.21 m, this can increase the potential and generated power of 82.56% Based on the analysis of the daily load, major load changes affect changes in voltage and frequency output of the imag, this was due to the load current controller can not work fast (slow response) to divert the major load changes to the load apparent (ballast load). There are several methods that can be done to control the voltage and frequency, one method of which is to adjust the load (dummy load). The results of the analysis will be in the form of recommendations for improvement so that the MHP and the frequency of the voltage instability can be obtained to ensure the quality of the electricity generated by Imag at MHP system.